Effect of submucosal fibrosis on endoscopic submucosal dissection of colorectal tumors: Pathologic review of 173 cases. Issue 5 (May 2015) - Lee, Sang Pyo; Kim, Jeong Hwan; Sung, In‐Kyung; Lee, Sun‐Young; Park, Hyung Seok; Shim, Chan Sup; Han, Hye Seung
Abstract Background and Aims Endoscopic submucosal dissection (ESD) is now commonly performed as a treatment for colorectal tumors. However, little is known about the relationship between submucosal fibrosis and the outcome of the colonic ESD procedure. The aims of this study were to investigate the relationship between the degree of submucosal fibrosis in colorectal tumors and the outcomes of ESD for these tumors and to evaluate the risk factors for submucosal fibrosis. Methods We retrospectively reviewed the records of patients with colorectal adenoma or carcinoma who had undergone an ESD, during a four‐year period from January 2010 to December 2013. The resected specimens were histologically examined after Masson's trichrome staining, and the severity of the submucosal fibrosis was classified as no fibrosis (F0), mild fibrosis (F1), or severe fibrosis (F2). Results Among a total of 173 cases (106 male, mean age 65.0 ± 10.2 years; F0 33, F1 78, F2 62) enrolled, 46 incidences of complications (perforation 19, post‐coagulation syndrome 21, bleeding 6) had developed. Multivariate analysis revealed that F2 fibrosis was significantly associated with the development of complications. Submucosal invasion and large tumor size (≥ 30 mm) were identified as independent predictors of F2 fibrosis. Conclusion Severe fibrosis is the most powerful risk factor for complications and can interfere with en bloc resections. The possibility of submucosal fibrosis should be considered, and the procedure should be cautiously performed in cases where the tumor diameter is greater than 30 mm and when submucosal cancer is suspected.